ASPEK FISIOLOGI RUMPUT GAJAH TERHADAP INTERVAL DAN TINGGI PEMANGKASAN SERTA PEMBERIAN AIR YANG BERBEDA - Adrianton, Adrianton (MEDIA LITBANG SULTENG, 2011)
The research was aimed at identifyingÂ physiology aspects of elephant grass to the cutting interval and height and different water giving. The research was carried out at experimental garden BPTP Gowa, Pa Bentengan Village Bajeng Sub-district Gowa Regency, South Sulawesi Province, carried out from May until September 2007. The research method was arranged based on split-plot-design in group random design consisting of three repetitions. The treatment arrangement was as follow: main plot S was with and without watering. Sub-plot was the cutting height (T) consisting of three levels, I,e. 10 cm cutting height from the ground surface, 20 cm cutting height from the ground surface, and 30 cm cutting height from the ground surface. The sub plots were the cutting interval consisting of three levels, i.e a-4-week cutting interval, a-6-week cutting interval, and an-8-week cutting interval. The research result showed than an-8-week cutting interval and 20 cm cutting height gave the highest mean at: photosynthesis speed, internal CO2 level, number of saplings, wet and dry weight of plants and small stomata conduct. Water giving gave the highest mean at: photosynthesis speed, internal CO2, numberÂ of saplings, wet and dry weight of plants, while without water giving gave the highest mean at stomata conduct and transpiration speed.